Trading Behavior During Stock Market Downturns: The Dow, 1915 - 2004 - Pierre L. Siklos; Martin T. Bohl (European University Viadrina, The Postgraduate Research Programme: Capital Markets and Finance in the Enlarged Europe, 2005)
Stock markets periodically experience sharp falls with some referred to as outright crashes. The extant literature has generally resorted to survey type evidence to determine the behavior of investors during such episodes. These kind of studies come to the conclusion that fundamentals play little role in explaining sharp stock market downturns as in October 1987. We know of no econometric study that asks whether feedback, momentum or trend chasing type behavior might explain the behavior of large stock market downturns. Resorting to a feedback trader model, we estimate a variety of asymmetric GARCH-type models. Based on daily data on the Dow Jones Industrial Average index since 1915 we find that there is evidence of positive feedback trading during episodes of stock market crashes. Hence, the econometric evidence is broadly consistent with findings based on surveys.
Keywords: G14; C22; 330; Börsenkrise; Wertpapierhandel; Anlageverhalten; Schätzung; USA; feedback trading